2012
DOI: 10.5539/hes.v2n2p79
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Taiwanese Aboriginal Students’ Educational Aspirations

Abstract: By analysing the national data from the Junior Survey of the Taiwan Higher Education Dataset, this study identified significant variables influencing the educational aspirations of aboriginal students at technical and vocational institutions. The study shows that several variables are predictive of the educational aspirations of aboriginal students. Institutional types, more weekly hours of lessons, more time spent on assignment preparation and revision, a higher maternal educational level, a higher GPA, a kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Interestingly, 67% of participants (e.g., four female students) reported that women are discouraged in part by stereotypes associating STEM fields with men and masculine traits, whereas 42% emphasized the positive impact of ethnicity (i.e., aboriginal students belong to ethnic minorities in high schools in Taiwan) on admissions to college/university. For example, there are some supportive and beneficial programs (e.g., special enrollment policies, scholarship) for aboriginal students in Taiwan (Hou & Huang, 2012). These findings support previous research investigating roles of gender and ethnicity in STEM career choice and participation (O’Brien, Blodorn, Adams, Garcia, & Hammer, 2015; Tien, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 67% of participants (e.g., four female students) reported that women are discouraged in part by stereotypes associating STEM fields with men and masculine traits, whereas 42% emphasized the positive impact of ethnicity (i.e., aboriginal students belong to ethnic minorities in high schools in Taiwan) on admissions to college/university. For example, there are some supportive and beneficial programs (e.g., special enrollment policies, scholarship) for aboriginal students in Taiwan (Hou & Huang, 2012). These findings support previous research investigating roles of gender and ethnicity in STEM career choice and participation (O’Brien, Blodorn, Adams, Garcia, & Hammer, 2015; Tien, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Limited job opportunities in rural areas have forced many indigenous parents to seek employment in bigger cities, entrusting their children to the care of one parent or grandparents; thus, the proportion of elementary and junior high school students raised Corresponding author: Hui-Ju Pai (huiju@ucsb.edu) by single parents or grandparents is significantly higher in indigenous tribes than it is in Taiwan as a whole (Lee, Chao & Chang, 2011). Single parenting or custodial grandparenting, combined with lower income earnings, poorer educational backgrounds, and lower literacy rates among indigenous parents and grandparents, have led to less parental supervision and homework assistance provided (Hou & Huang, 2012;Lin, 2000;Wu, 2009;Wang, 2009). Additionally, the rise in teacher turnover and lack of parent-teacher interaction (Chen, 1997;Chen, 2001) have led to the characterization of indigenous schooling as "the dark corners of national education" (Chen, 2007, p.4).…”
Section: Indigenous Education In Taiwanmentioning
confidence: 99%
“…The situation has improved steadily. In 2010, 82.95 percent of indigenous students enrolled in high school (Hou & Huang, 2012), a number which has recently risen to 95 percent (Council of Indigenous Peoples, 2018); however, their university enrollment rate is still lower than that of non-indigenous Taiwanese students at 54 percent (Council of Indigenous Peoples, 2018), and their dropout rate is higher (Hou & Huang, 2012). Taiwanese studies that evaluate English proficiency based on ethnicity have found that indigenous students perform lower than their Han counterparts (Yang, 2007).…”
Section: Indigenous Students' English Learning Challenges-empiricalmentioning
confidence: 99%
“…Until recently, issues related to the Taiwanese indigenous academic achievement gap had not been thoroughly researched (Hou & Huang, 2012), making it an area worthy of further study. While the Taiwanese government has tried to address the problem by lowering the standards necessary for indigenous students to gain access to tertiary education, this might only delay-rather than solve-the negative consequences of the achievement gap, as indigenous students have a higher drop-out and deferment rate in universities (Hou & Huang, 2012). Indigenous students likely find it frustrating to be in classes where the material is geared to students who have a 25 percent higher average than they do.…”
Section: Introductionmentioning
confidence: 99%